"Where Your Ethnic Kids Go": How Counselors as First Responders Legitimate Proper Course Placements for Community College Students. Issue 4 (3rd April 2019) - Maldonado, Carlos
ABSTRACT: Previous research on remediation has examined course placement practices, but little is known about first responders and how their beliefs about proper course placements help maintain patterns in course access. This study examined how taken-for-granted racial beliefs were used as legitimate knowledge by community college counselors. Haney López's (2000) race as commonsense theoretical perspective was used to analyze interview data from 34 counselors in 2 southern California community colleges. Data showed that counselors recreated race categories and racial hierarchy, and they did so by reinforcing beliefs about white students as intelligent and deserving higher placements and Latina/o students as comparatively lower in ability and deserving remediation. The results suggest that counselors begin institutionalizing racial sorting immediately as first-time students begin to enroll. The findings highlight the importance of racial mindfulness in policy, practice, and research.